THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, WORK MOTIVATION, AND JOB SATISFACTION ON EMPLOYEES’ PERFORMANCE - Anindya , Ajeng Kartika Ayu; Tohir; Jati, Eling Purwanto (Terbuka Journal of Economics and Business, 2020)
This study aims to determine the effect of transformational leadership, work motivation, and job satisfaction on employees performance in PDAM Brebes Regency office. The method used in this study is survey method that involved 116 respondents. The data gained were analyzed using validity test, reliability test, path analysis, and hypothesis testing. The results of this study and calculation data from Path Analysis show that transformational leadership, work motivation, job satisfaction affect employees’ performance.